FoodNet - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
FoodNetThe FoodNet project in Uganda is a joint venture involving, amongst others, government services, the International Institute of Tropical Agriculture, and CTA.The particular interest in the MIS operated by FoodNet is the way it seeks to serve...